Skin-Derived Stem Cells for Wound Treatment Using Cultured Epidermal Autografts: Clinical Applications and Challenges - Inga Brockmann; Juliet Ehrenpfordt; Tabea Sturmheit; Matthias Brandenburger; Charli Kruse; Marietta Zille; Dorothee Rose; Johannes Boltze (Stem Cells International)
The human skin fulfills important barrier, sensory, and immune functions—all of which contribute significantly to health and organism integrity. Widespread skin damage requires immediate treatment and coverage because massive skin loss fosters the invasion of pathogens, causes critical fluid loss, and may ultimately lead to death. Since the skin is a highly immunocompetent organ, autologous transplants are the only viable approach to permanently close a widespread skin wound. Despite the development of tissue-saving autologous transplantation techniques such as mesh and Meek grafts, treatment options for extensive skin damage remain severely limited. Yet, the skin is also a rich source of stem and progenitor cells. These cells promote wound healing under physiological conditions and are potential sources for tissue engineering approaches aiming to augment transplantable tissue by generating cultured epidermal autografts (CEAs). Here, we review autologous tissue engineering strategies as well as transplantation products based on skin-derived stem cells. We further provide an overview of clinical trial activities in the field and discuss relevant translational and clinical challenges associated with the use of these products.